2020
DOI: 10.1101/2020.11.29.403154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Flip-Flops III: Stomatogastric Ganglion

Abstract: The stomatogastric ganglion (STG) is a group of about 30 neurons that resides on the stomach in decapod crustaceans. Its two central pattern generators (CPGs) control the chewing action of the gastric mill and the peristaltic movement of food through the pylorus to the gut. The STG has been studied extensively because it has properties that are common to all nervous systems and because of the small number of neurons and other features that make it convenient to study. So many details are known that the STG is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This article is the fourth in a series of articles that show how neurons are likely to be connected to perform certain Boolean logic functions with networks composed of neural flip-flops (NFFs). The first three articles [1][2][3] showed that NFFs and NFFs configured as central pattern generators (CPGs) can produce the major phenomena of short-term memory, electroencephalography, and the lobster's stomatogastric ganglion.…”
Section: Introductionmentioning
confidence: 99%
“…This article is the fourth in a series of articles that show how neurons are likely to be connected to perform certain Boolean logic functions with networks composed of neural flip-flops (NFFs). The first three articles [1][2][3] showed that NFFs and NFFs configured as central pattern generators (CPGs) can produce the major phenomena of short-term memory, electroencephalography, and the lobster's stomatogastric ganglion.…”
Section: Introductionmentioning
confidence: 99%